A MATEMÁTICA POR TRÁS DO OLHAR DA MONA LISA - Maroski, Marcelo Wachter; Dorneles, Lecir Dalabrida; Piva, Claudia; Spilimbergo, A. Patricia Grajales (Salão do Conhecimento, 2017)
Trabalho desenvolvido através de projeto de extensão da UNIJUÍ.